PT Serabut Nusa Berdaya omnichannel strategy in promoting its products and services - Dimas Herdy; Yanuar Luqman (SEAN Institute, 2024)
The world of advertising in this era is developing very rapidly, as can be seen from the number of companies or MSME businesses that utilize new media (digital media). Many brands and companies carry out advertising campaigns using new media as a form of strategy to keep up with developments and demands of the times. Serabut Nusa Berdaya has the aspiration of becoming a forum for Indonesian MSMEs that provides equal opportunities in business competition and modernization. One of the technologies that is currently becoming a trend is technology and strategy through digital media or often referred to as digital marketing. The method used is descriptive qualitative, with data collection through interviews, observation and documentation. The research results show that PT Serabut Nusa Berdaya's omnichannel strategy consists of 6 points, namely: 1) Customer experience / focus on customer experience, in the form of friendliness and real time response as well as providing discounts for those who join the live stream channel at Serabut Nusa. 2) Preparing a marketing plan, by knowing the benefits and advantages of your own product, then researching competitors, and personalizing each social media platform. Apart from that, it is also collecting information, disseminating information. 3) Segmentation of prospects and personalization of business flows, the segmentation used is geographic segmentation. People tend to have difficulty finding delicious, unique, cheap and quality food souvenirs. 4) Context marketing / relevant context, the strategy used is to provide trending content but still carry the character of Fiber Nusa. 5) Use the right automation marketing tools, the automation tool used is Facebook Creator Studio (Facebook & Instagram). 6) Customer-centric business, Serabut Nusa Berdaya places both consumers and potential consumers as friends to establish synergistic communication with the aim of increasing customer loyalty.